2015
DOI: 10.1186/s12913-015-0832-1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of care seeking for obstetric complications in rural northwest Bangladesh: analysis from a prospective cohort study

Abstract: BackgroundIn communities with low rates of institutional delivery, little data exist on care-seeking behavior for potentially life-threatening obstetric complications. In this analysis, we sought to describe care-seeking patterns for self-reported complications and near misses in rural Bangladesh and to identify factors associated with care seeking for these conditions.MethodsUtilizing data from a community-randomized controlled trial enrolling 42,214 pregnant women between 2007 and 2011, we used multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
25
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 54 publications
16
25
2
Order By: Relevance
“…Care-seeking from a trained provider was associated with both women’s and husband’s literacy for both antepartum and intrapartum complications; these findings were consistent with the findings of an earlier study in Bangladesh where women’s literacy was associated with seeking care from a qualified provider for obstetric complications [15]. Women’s literacy and household wealth status are important factors and are considered as proxies of women’s decision making ability, empowerment and affordability for maternal health care utilization [23, 24].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Care-seeking from a trained provider was associated with both women’s and husband’s literacy for both antepartum and intrapartum complications; these findings were consistent with the findings of an earlier study in Bangladesh where women’s literacy was associated with seeking care from a qualified provider for obstetric complications [15]. Women’s literacy and household wealth status are important factors and are considered as proxies of women’s decision making ability, empowerment and affordability for maternal health care utilization [23, 24].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, women who were living in a distance of less than 10 km of a health facility were more likely to seek trained care for both antepartum and intrapartum complications. This finding is consistent with findings of a number of studies conducted in Bangladesh and elsewhere [12, 15]. In a study conducted between 2007 and 2011 in Bangladesh, Sikder et al showed that living within 10 km from the health facility was associated with seeking formal care for intrapartum complications [15].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations